Social capital and happiness in university students: a higher-order analysis - Mian Muhammad Ahmad Iqbal; Qaisar Khalid Mahmood; Muhammad Saud; Nadir Hayat (International Journal of Adolescence and Youth, 2023)
ABSTRACTSocial capital is a valuable asset in community psychology for the growth of happiness. The various components of social capital, including trust and reciprocity, help youth to function positively in society. Unfortunately, previous literature ignored a higher-order analysis of social capital with happiness. This research aimed to examine the association between various components of social capital and happiness. Using a convenient sampling technique, we gathered data from 843 university enrolled students (Male = 581, Female = 262, age 21–23) from four public universities in Punjab, Pakistan. The first and second hypotheses confirmed that bonding trust, bonding, bridging, and linkage engagements and components of social capital were positively associated with the happiness of youth. The higher-order social capital model should be replicated in future studies, and local government should take essential steps to get the trust of the people which is necessary for the development of society.